KEBIJAKAN PENGELOLAAN PAJAK DAERAH DALAM KERANGKA PENYELENGGARAAN OTONOMI DAERAH (ANALISA TERHADAP IMPLEMENTASI WEWENANG PENGELOLAAN PAJAK DAERAH OLEH PEMERINTAH PUSAT DAN PEMERINTAH DAERAH) - Kadar Pamuji (Jurnal Dinamika Hukum, 2014)
Regional autonomy is the right, authority, and duty to regulate autonomous regions and manage their own affairs and interests of local communities in accordance with the legislation. One of which is owned by the local authority is the authority to impose taxes. Supporting local autonomy, the local tax management policies cannot be separated from the regional autonomy policy direction outlined by the Central Government. Local Government as implementing regional autonomy in the management of local taxes tends to be subject to the rules specified by the Central Government. Changes of local tax management policies show that the government has no found raw format in the management of local taxes management yet. Management of local taxes does not show the direction to the actual implementation of regional autonomy due to dominant intervention by the central government.Key words : policy, local taxes, local autonomy